From a Cross-Cultural Perspective, Modern Art Expression: Analyzing how Artists from Different Cultural Backgrounds Express Their Views and Emotions through Visual Art - He Shiyue (SHS Web of Conferences)
The purpose of this article is to analyze modern art expression from a cross-cultural perspective, emphasizing the use of visual art as a means for expressing personal opinions and emotions among artists from a variety of cultural backgrounds. A phenomenon of multicultural integration has been observed in the modern art world as a result of globalization. Artworks are not only a means for artists to express their emotions, but also a communication tool to overcome cultural barriers. Studying the creations of artists from different cultural backgrounds can reveal how artistic expression is influenced by personal experiences and cultural values, and further discuss the impact of global cultural interactions on artistic styles and themes.